In Silico, In Vitro and In Vivo Assessment of Acetylcholinesterase Inhibitory Activity of Theobromine Derivatives Containing an Arylpiperazine Fragment - Andonova, Lily; Georgieva, Maya; Atanasova, Mariyana; Valkova, Iva; Doytchinova, Irini; Simeonova, Rumyana; Zheleva-Dimitrova, Dimitrina; Zlatkov, Alexander (Letters in Drug Design & Discovery, 2023)
Background: In the current Alzheimer’s disease therapy as the preferred treatment are applied acetylcholinesterase inhibitors. Aiming to identify the active pharmacophores necessary for increased acetylcholinesterase inhibitory activity, some docking studies have been applied. Methods: In silico docking evaluation of the binding modes, identification of acetylcholinesterase inhibitory activity in vitro through Ellman’s test and ITC protocol, and the in vivo effect. PAMPA evaluation of the GIT and BBB permeability. Results: In the present study, two series previously synthesized in our laboratory, arylpiperazine derivatives of theobromine, were docked into the rhAChE active sites. Ellman’s test outlined molecules LA1 and LA7 as the most active, with IC50 of 0.708 and 0.299 μM, respectively. In the acute toxicity test, LA7 given intraperitoneally in mice showed moderate toxicity with LD50 of 87.5 mg/kg. The new compound, administered i.p. for 12 days at doses 2 mg/kg/day and 4 mg/kg/day, respectively, showed a pronounced acetylcholinesterase inhibitory activity in vivo. Conclusion: The corresponding binding modes were identified, where the docking pose for the studied molecules depends on the protonated state of the nitrogen atom of the piperazine moiety. In the best scored pose for LA7, the xanthine moiety is bound into the catalytic active site (CAS) of acetylcholinesterase, while the arylpiperazine fragment is placed into the peripheral binding site (PAS). For the evaluated selected structures, good permeability through the GIT and BBB assessed by PAMPA was also determined.
Keywords: Ellman’s test